Overcoming Endoplasmic Reticulum Stress in iPSC-Derived Beta Cells: Advancing Therapies for Diabetes - Meneses Rêgo, Amalia Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2024)
Pancreatic beta cell dysfunction is a central feature of diabetes mellitus, where prolonged metabolic stress contributes to cell failure and death. A significant driver of this dysfunction is endoplasmic reticulum (ER) stress, which leads to impaired insulin secretion and beta cell loss. The recent development of induced pluripotent stem cells (iPSCs) offers an innovative approach to generating patient-specific beta cells, presenting a potential breakthrough in diabetes treatment. However, a significant challenge remains iPSC-derived beta cells are particularly vulnerable to ER stress, which hampers their functionality and survival after transplantation. This review provides a detailed analysis of the effects of ER stress on iPSC-derived beta cells, focusing on the molecular mechanisms that trigger the unfolded protein response (UPR) a crucial pathway activated to manage protein misfolding and cellular stress. The review examines current therapeutic strategies to alleviate ER stress, including pharmacological agents and genetic interventions designed to modulate the UPR to improve beta cell resilience and function in diabetic conditions. By synthesizing recent findings, this review highlights critical gaps in the research and proposes future directions to optimize iPSC-derived beta cell therapies. Addressing ER stress is crucial to unlocking the full therapeutic potential of these cells, paving the way for more effective and long-lasting diabetes treatments. This article aims to capture the current state of research and inspire further exploration into overcoming one of the most significant barriers in beta cell replacement therapy.